Optimal modulation and coding scheme selection in cellular networks with hybrid-ARQ error control - Kim, Dongwook; Jung, Bang; Lee, Hanjin; Sung, Dan; Yoon, Hyunsoo (IEEE transactions on wireless communications, 2008)
We propose an optimal modulation and coding scheme (MCS) selection criterion for maximizing user throughput in cellular networks. The proposed criterion adopts both the Chase combining and incremental redundancy based hybrid automatic repeat request (HARQ) mechanisms and it selects an MCS level that maximizes the expected throughput which is estimated by considering both the number of transmissions and successful decoding probability in HARQ operation. We also prove that the conventional MCS selection rule is not optimized with mathematical analysis. Through link-level and system-level simulations, we show that the proposed MCS selection criterion yields higher average cell throughput than the conventional MCS selection schemes for slowly varying channels.